Academic Leadership for Fieldwork Coordinators : A Guide to Facilitation and Coordination. - Jones, Sue; Ladyshewsky, Richard; Smith, Megan; Trede, Franziska; Flavell, Helen; Chapman, Rose (Office for Learning and Teaching, 2013)
Guide for facilitators and coordinators produced as a result of a project that developed and piloted a tailored leadership development program for Fieldwork Coordinators (FCs). It built on the success of an earlier Australian Learning and Teaching Council funded project 'Leading Courses' that employed a distributed leadership approach to develop the leadership capabilities of Course Coordinators or Program Heads. In the context of Leading Fieldwork, FCs are those academic staff responsible for ensuring high quality student learning experiences through a practicum, professional experience, internships, clinical placements, or fieldwork. The Leading Fieldwork project has resulted in a comprehensive and cohesive academic leadership development program specifically designed for FCs. Data collected during the project suggests that FCs are dedicated staff who are committed to their students. However, workload, resourcing issues and a lack of development opportunities, have resulted in a tendency for FCs to focus on operational roles and 'getting the job done' rather than the crucial strategic areas of innovation and relationship building with placement providers and industry. Importantly, the Academic Leadership for Fieldwork Coordinator Program(ALFCP) provides some solutions to these challenges by providing a structured program to enable the identification of the individual leadership development needs of FCs. The ALFCP resulted in a change in participant perceptions of the role as one of leadership, an understanding of the need to 'manage up,' a shift from operational to strategic aspects of the role, and an ability to identify fieldwork coordination within the ICVF and the importance of each of the six ICVF leadership roles. A wide range of impacts from the ALFCP were reported including: the development of information and resources for FCs; changes to WIL in specific units of study; and one participant reported that the ALFCP led them to initiate a forum with industry partners to build community engagement and strengthen partnerships.